Shipborne Observations of Chemical Characterization and Light Extinction of Aerosol Along the Yangtze River, China - Chen, Dong; Zhao, Qiuyue; Li, Li; Xia, Sijia; Chen, Feng; Wei, Mengqi; Li, Huipeng; Zhang, Lei; Guan, Miao (Frontiers in Environmental Science, 2022)
The study of air quality over the Yangtze River is important for the pollution of urban agglomeration along the longest river in China. A comprehensive 15-day shipborne observation was conducted in the Yangtze River of the Jiangsu section in the summer of 2019. Through online observation and offline chemistry analysis of aerosol and gaseous pollutants, the result showed that the air pollution over the Yangtze River was more severe than that in surrounding cities. Sulfate, nitrate, and ammonium (SNA) dominated the water-soluble inorganic species and accounted for 35.0% ± 7.3% of the fine particle concentration (PM2.5) along the Yangtze River. The high concentration of sulfate in the droplet mode (0.56–1.0 μm) was due to the formation of sulfate through in-cloud processes under high sulfur dioxide (SO2) concentration by ship emission and high relative humidity along the river. The strong correlation between the measured mass absorption efficiency value by carbon analyzer and that simulated based on the assumption of core–shell suggested that the core–shell mode was the main composition form of aerosol in the Yangtze River. The scattering effect was the main part of the aerosol light extinction, and the scattering coefficient of 0.4- to 1.1-μm particles accounted for 85.0% of the total extinction coefficient. Positive matrix factorization model was applied for the source apportionment of particle size segment of main extinction contribution (0.4–2.1 μm), and the result showed that secondary nitrate, ship emission, coal combustion, fugitive dust, and biomass burning were the main sources of aerosols in the Yangtze River. After source reanalysis, the result indicated that the contribution of secondary nitrate from nitrogen oxide (NOx) by ship emission and coal combustion should not be ignored.